Impact of brine and antiscalants on reef-building corals in the Gulf of Aqaba – Potential effects from desalination plants. (1st November 2018) - Petersen, Karen Lykkebo; Paytan, Adina; Rahav, Eyal; Levy, Oren; Silverman, Jacob; Barzel, Oriya; Potts, Donald; Bar-Zeev, Edo
Abstract: Seawater reverse osmosis (SWRO) is becoming an increasingly important source of potable water in arid and semi-arid regions worldwide. Discharge of brine-effluent from desalination facilities has been shown to significantly impact coastal marine ecosystems ranging from seagrass meadows to microbial communities. In this study, we examined the impacts of increased salinity (10% above ambient) and presence of antiscalants (0.2 mg L −1, polyphosphonate-based) on three reef-building coral species; Stylophora pistillata, Acropora tenuis and Pocillopora verrucosa, from the Gulf of Aqaba (northern Red-Sea). Our results indicate that the corals, as well as associated bacteria and algae, were significantly impaired by the elevated salinity and antiscalants, leading to partial bleaching. Specifically, the abundance of bacteria and symbiotic algae as well as calcification rates were typically lower (20–85%, 50–90% and 40–50%, respectively) following incubations with both amendments. However, the impact of desalination brine was often species-specific. Thus, we propose that the ecotoxicological criteria used for hard corals should be determined based on the sensitivity of key species in the community dominating the area affected by desalination discharge. Highlights: Salinity 10% above ambient and polyphosphonate antiscalants have clear impacts on coral's physiology. Salinity 10% above ambient and polyphosphonate antiscalants significantly reduced bacteria and Symbiodinium abundances. Calcification rates decreased following the addition of salt and polyphosphonate antiscalants. Variable responses to increased salinity among coral species suggests species-specific sensitivity.